THE BENEFITS OF MULTILINGUALISM TO PERSONAL AND PROFESSIONAL DEVELOPMENT (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Multilingualism provides numerous cognitive, social and professional advantages. Research indicates that multilingual individuals often exhibit stronger problem-solving abilities, cognitive flexibility and empathy. Professionally they tend to have increased employability, adaptability and communication skills. This article explores these benefits, reviewing evidence that supports multilingualism’s positive impact on personal and career growth.